Praktikum Pembuatan Kalorimeter Sederhana untuk Menstimulus Pemahaman Peserta Didik Kelas XI MIPA 5 di SMAN 1 Cikeusal - Ratna Sari Siti Aisyah; Dinda Nur Rahmah; Elsa Oktaviani Sopyan; Iim Khotimah; Irma Sukmawati; Lismanda Islamiah; Mutiara Aristawidia; Siti Hana Irawarni Alfu; Pipih Muspiroh (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2023)
This research aims to stimulate the understanding of Class XI MIPA 5 students at SMAN 1 Cikeusal through practical work on making a simple calorimeter. This activity was carried out at SMAN 1 Cikeusal. Through this research, it is hoped that students' perception of chemistry subjects as difficult, boring, scary and so on can slowly be reduced so that students' understanding of chemistry subjects can increase. The research method carried out was through a series of activities at SMAN 1 Cikeusal, namely carrying out practical work on making a simple calorimeter using simple tools and materials that are easily found in the surrounding environment and comparing the simple calorimeter tool with the real tool. This activity was held on Wednesday 11 October 2023, which was attended by students of SMAN I Cikeusal Kab. Serang consisting of representatives from class XI Mipa 5 with a total of 40 participants. In carrying out this activity, students showed an enthusiastic and enthusiastic attitude in participating in the learning process, especially during simple practical activities so that the chemical material being studied, namely simple calorimeters, could be understood well. Thus, the aim of the research at SMA 1 Cikeusal can be said to have been achieved because the learning outcomes of students in class XI MIPA 5 SMAN 1 Cikeusal experienced a significant increase after carrying out practicum activities. This is proven by the results of the pretest average score of 87 increasing to 93.5.